The ABC of EU law (Luxembourg, 2017)
"The legal order created by the European Union shapes our political life and society. Individuals are not merely citizens of their country, town or district; they are also Union citizens. 'The ABC of EU law' by Prof. Klaus-Dieter Borchardt examines the roots of the European project and its development as a legal order, and is a definitive reference work on the subject. It is intended for interested readers who would like an initial insight into the structure of the Union and the supporting pillars of the European legal order."